Histopathological role of vitamin D deficiency in recurrent/chronic tonsillitis pathogenesis: Vascular epithelial growth factor‐mediated angiogenesis in tonsil. Issue 3 (25th February 2022) - Safak, Ayse S.; Bulut, Fuat; Cumbul, Alev
Abstract: Objectives: Our aim in this study is to reveal the role of vitamin D deficiency in the pathogenesis of recurrent/chronic tonsillitis and to determine the expression of vascular epithelial growth factor (VEGF). Material and Methods: This study was conducted between September and February. Thirty‐two patients between the ages of 3 and 35 (mean age 9.71) with recurrent episodes of chronic tonsillitis were selected. Patients were divided into four groups according to their 25OHD levels. Patients with 25OHD levels 0–10 ng/ml were determined as Group 1, 11–20 ng/ml Group 2, 21–30 ng/ml Group 3, and 31–50 ng/ml control Group 4. Routine histological tissue sampling was performed for histopathological evaluation of the tonsillar tissues under light microscope (LM). Five micron sections were taken from the paraffin blocks and stained with Hematoxylin Eosin (HE) and Trichrome Masson (TCM). VEGF expression was examined immunohistochemically for each group. Results: Our analysis showed VEGF expression in all study groups (32 tonsillar tissues). Group 1 and Group 2 histopathological scores were significantly higher than the other groups ( p  < .001). There were significant differences in VEGF expressions between the four groups ( p  < .001). 25OHD levels of the patients in Groups 1 and 2 with strong VEGF expression were significantly lower than the other groups ( p  < .001). Conclusions: In conclusion, this study showed an increased angiogenesis in tonsil and an increase in VEGF expression of the tonsillar surface epithelium when blood serum 25OHD levels <20 ng/ml.